Learning behavior, digital platforms for learning and its impact on university student’s motivations and knowledge development - Noor, Uzma; Younas, Muhammad; Saleh Aldayel, Hessah; Menhas, Rashid; Qingyu, Xu (Frontiers in Psychology, 2022)
Background: Learning digital technologies in higher education is a process of knowledge generation, and the rapid growth of technology in education has a significant impact on students' learning behaviors, motivation, and knowledge development. Pakistan's remarkable technological breakthrough has increased in the education field. Study Objectives: The study focuses on estimating students' learning behaviors, identifying the positive influence of educational apps on digital learning platforms, and analyzing their impact on student's motivation and knowledge development. Methods: According to the study's objectives, a questionnaire survey was conducted to gather the primary data. The participants were students of universities in Lahore city of Pakistan. For this study, the sample size was N=300, carefully chosen using the purposive sampling technique. Of the respondents, there were 146 male and 154 female students, and the sample consisted of individuals aged 25 to 35. Smart-PLS 3.2.9 and the structural equation model (SEM) were applied to get the appropriate outcomes from the proposed study framework. Results: SEM analysis results shows that all proposed hypotheses (Animated Movies -> Student Motivation, Educational Apps -> Knowledge Development, Learning Behavior -> Animated Movies, Learning Behavior -> Educational Apps, Learning Behavior -> Knowledge Development, Learning Behavior -> Virtual Classrooms, Virtual Classrooms -> Knowledge Development, Virtual Classrooms -> Student Motivation) are confirmed while (Learning Behavior -> Student Motivation) is not confirmed. Conclusion: This study found that digital learning platforms significantly impact students' learning and what motivates them to learn. The study also found that using educational apps and virtual classrooms more often helps students learn more and be more motivated to learn.